Two new species of Mooreonuphis (Annelida: Onuphidae) from Australia - Paxton, Hannelore (Zootaxa, 2018)
Two new species of Mooreonuphis, a genus best known from the coasts of the Americas, are described from Australia, bringing the number of recognized Mooreonuphis species to 23. Mooreonuphis ariasi n. sp. was collected from off Sydney to Wollongong, New South Wales in sandy sediments, in depths of 25–50 m and M. wilsoni n. sp. in the Bass Strait and Tasmania, in 89–130 m. The two new Australian species are among the smallest and the only known abranchiate species in the genus. The summer collections of M. ariasi n. sp. contained a large number of brooders with their young undergoing asynchronous direct development in the parental tube. Nothing is known about the development of M. wilsoni n. sp.